Social Representations of COVID-19 Among Brazilian Elderly Women: A Structural Approach - Cardoso Ferreira, Alda Vanessa (2022)
Background: In January 2020, the World Health Organization declared the coronavirus disease 2019 (COVID-19) «a public health emergency of international concern» owing to the detection of cases and the rapid spread of the disease. Objective: This study aimed at understanding the social representations of COVID-19 among Brazilian elderly women. Method: A total of 100 elderly women selected by convenience sampling, with an average age of 69.24 years old (SD = 6.58), participated in the study. Data were collected online using a sociodemographic questionnaire and a free word association test (FWAT) with the stimulus word «COVID-19.» The responses were examined by prototypical analysis through IRaMuTeQ. Results: The social representations of COVID-19 emphasize death and fear of the disease caused by the novel coronavirus. Elements associated with measures to contain the virus are also part of the representational field. Conclusions: Understanding social representations of COVID-19 in elderly women may contribute to short- and long-term interventions to reduce the psychosocial consequences of COVID-19 in this age group.